Rancang Bangun Sistem Informasi Presensi Siswa di SMA Negeri 1 Ciseeng dengan Metode Extreme Programming - fauzan respati indira; Naufal Respati Indira; Raja Alief Alkahfi; Roeslan Djutalov (Journal of Research and Publication Innovation, 2023)
The rapid development of information technology has had a positive impact on increasing the effectiveness and efficiency of educational activities. Computers have an extraordinary ability to process data quickly, accurately and efficiently so that they can provide information at the right time. The attendance system is mandatory in education as a recorder of student attendance at SMA Negeri 1 Ciseeng, attendance is used as a reference for attendance, from attendance it can be seen the number of student attendance and student information for homeroom teacher reports to parents at the end of the semester. Recording student attendance with a manual system has many weaknesses, such as recording errors, multiple attendance, and students often work together with friends to skip school. Therefore, the school needs to improve performance in information processing to ensure that the process is carried out efficiently and effectively, as well as saving time and effort.